Konsep Dan Implementasi Pendidikan Pranikah Dalam Islam Bagi Calon Pengantin (Penelitian di Kantor Urusan Agama Kecamatan Sukawening Garut) - Sulaiman, Husnan; ILYAS, MOH HARISUDIN (STAI Al-Musaddadiyah Garut, 2025)
Family and education are the primary pillars in building a society. The family provides emotional, moral, and character support, serving as the foundation for every individual. Education, on the other hand, equips individuals with the knowledge and skills needed to face contemporary challenges. A harmonious family and quality education create individuals who are competitive, ethical, and prepared to contribute positively to society. Understanding and strengthening the roles of these two institutions are essential for collective progress and well-being. Furthermore, the family also functions as an informal educational institution, alongside schools and communities. This study aims to describe: (1) the concept of premarital education for prospective brides and grooms in Islam; (2) the implementation of premarital education for prospective brides and grooms at the Religious Affairs Office (KUA) in Sukawening District, Garut; and (3) the outcomes of premarital education conducted by KUA for the community in Sukawening District, Garut. This research involves a series of scientific activities aimed at solving a specific problem. The research method used is descriptive qualitative, with the researcher serving as the key instrument. Data collection techniques include: (1) primary sources such as observations, interviews, and documents; and (2) secondary sources such as books or other relevant information. The study concludes that the concept of premarital education at KUA Sukawening village in Sukawening District is recognized as a highly effective program for equipping prospective brides and grooms with the knowledge and skills needed to face married life. Despite some shortcomings, proper and comprehensive guidance helps couples confront the realities of marriage with greater awareness and understanding. Keywords: Concept, Education, Premarital, Islam, Prospective Brides and Grooms